Practice nurses need better diabetes education to meet service and individual needs. (2nd November 2019) - Phillips, Anne
Abstract : Anne Phillips, from the iDEAL advisory group, highlights the need for constant evidence-based educational opportunities to be available and accessible, via a variety of means, to ensure practice nurses can keep up to date and deliver evidence-based diabetes care